Seasonal endocrine changes in steroid hormones of developing ovarian follicles in Surti buffaloes - PARMAR, A P; MEHTA, V M (The Indian Journal of Animal Sciences, 2013)
The effect of development of ovarian follicles and seasons on oestradiol-17 beta and progesterone levels was studied in Surti buffaloes. The peak oestradiol-17 Beta levels were recorded influid coUected from follicles 5-8 mm in diameter. The progesterone level in follicular, fluid tended to increase with the increase in follicular diameter. Significantly lower (p<0.01) leveh of oestradiol-17 Beta were recorded in all the stages of follicular development during summer. However, the progesterone level was significantly higher (p<0.01) in summer than in winter and monsoon.